Corporate Social Responsibility as a Moderator of Good Corporate Governance with Company Performance - Difinubun, Yusron; Sismar, Andi (Pusat Penerbitan dan Publikasi Ilmiah, FEB, Universitas Muslim Indonesia, 2025)
Purpose: This study examines the influence of Corporate Social Responsibility (CSR) as a moderating variable in the relationship between Good Corporate Governance (GCG) and corporate financial performance in manufacturing companies listed on the Indonesia Stock Exchange. Research Design and Methodology: This quantitative study uses CSR, GCG, and Financial Performance (proxied by Financial Discretionary) as research variables. The sample comprises 23 manufacturing companies listed on the Indonesia Stock Exchange from 2020 to 2022. Data were analyzed using descriptive statistics and moderated regression analysis with the assistance of SPSS 25.0. Classical assumption tests were conducted before hypothesis testing to validate the data. Findings and Discussion: The findings indicate that corporate social responsibility has a substantial impact on corporate financial performance. Moreover, CSR significantly moderates the relationship between Good Corporate Governance and economic performance. The results suggest that the presence or absence of CSR practices affects how GCG impacts a company's financial outcomes, indicating that CSR plays a critical role in strengthening or weakening governance structures. Implications: The study contributes to the theoretical understanding of CSR's strategic role and provides practical insights for corporate managers and regulators. Enhanced CSR practices foster stakeholder trust and enhance governance effectiveness, leading to improved financial results.